SIGNALS GENERATED BY A SENSOR THAT CAPTURES THE CANTILEVER DEFLECTION OF THE ATOMIC FORCE MICROSCOPE WITH NONLINEAR BEHAVIOR - Nozaki, Ricardo; Navarro, Helio A.; Brasil, Reyolando; Pereira da Silva, Marcelo A.; Tusset, Angelo M.; Bueno, Atila M. [UNESP]; Balthazar, Jose M. [UNESP]; ASME (Amer Soc Mechanical Engineers, 2015)
This paper presents results obtained numerically by an experimental approach. The sensor of the atomic force microscope generated cantilever deflections series that were recorded in data files as a function of time and as a function of tip-sample distance. With these series of deflections, we attempted to adjust parameters and refine models of classical oscillators atomic force microscope, making them more sensitive to tip-sample distance, through the method of system identification proposed by [12]. This method allows us to choose any model and, through its analytical solution, compare the results obtained with the experiment. The reconstruction of the state space is done with the intention of observing different phase portraits for different distances between sample-tip.